Analisis Kesalahan Berbahasa Kesalahan Penggunaan Partikel Sa- dan Sawfa pada Pelajar SMA Pondok Pesantren As-Sa’adah - Muhamad Raihan; Faisal Hendra (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the errors in the usage of the particles sa- and sawfa by high school students at Pondok Pesantren As-Sa’adah. These particles in Arabic express the future, but differ in usage and meaning. Errors in their use can cause confusion in sentence interpretation. This descriptive qualitative study used error analysis, collecting data through written tests and interviews. Results show common errors include interchangeable use of sa- and sawfa without considering time context. Factors include limited understanding of time concepts and insufficient practice. The study recommends improved teaching methods and contextual exercises to enhance student comprehension.